Surrogacy: A biomedical mechanism in the fight against infertility - Barać Ivana (Anali Pravnog Fakulteta u Beogradu)
This paper reviews the issue of surrogacy. The author analyzes surrogacy and continues by conducting a comparative overview of two legal systems with different approaches to surrogacy. The analysis first looks at the legal system of Russia, as it represents a country that allows all forms of surrogacy, and then that of Germany, as a country with norms prohibiting all forms of surrogacy. In turn, the author reviews Serbian legal provisions, which also forbid all forms of surrogacy. The paper further explores whether there is justification for such legal provisions, i.e., it pinpoints potential problems that could arise if the legal provisions were to be changed. It is concluded that the Serbian legislator has decided to remain silent on this issue, most probably due to the fact that any amendments could raise questions that, at least for the time being, have no clear answers.